Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s40824-023-00339-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineered exosomes enriched in netrin-1 modRNA promote axonal growth in spinal cord injury by attenuating inflammation and pyroptosis

Abstract: Background Spinal cord injury (SCI) brings a heavy burden to individuals and society, and there is no effective treatment at present. Exosomes (EX) are cell secreted vesicles containing molecules such as nucleic acids and proteins, which hold promise for the treatment of SCI. Netrin-1 is an axon guidance factor that regulates neuronal growth. We investigated the effects of engineered EX enriched in netrin-1 chemically synthetic modified message RNA (modRNA) in treating SCI in an attempt to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…ModRNAs, which are novel gene vectors, are transferred into target cells to achieve facile and controllable expression of target proteins. ,, Moreover, encapsulation of medications within exosomes can prevent monocyte phagocytosis and enzymatic degradation in the cellular matrix in vivo . To enhance the therapeutic efficacy, MSCs are often genetically modified by exogenous genetic transfection based on disease-specific characteristics. ,, To enhance the therapeutic potential of exosomes and improve the prognosis of OA, we used modRNA technology to genetically modify exosomes with Atf5. This study confirmed that Ex modAtf5 released from Gel@Ex modAtf5 were highly effective in preventing OA progression in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ModRNAs, which are novel gene vectors, are transferred into target cells to achieve facile and controllable expression of target proteins. ,, Moreover, encapsulation of medications within exosomes can prevent monocyte phagocytosis and enzymatic degradation in the cellular matrix in vivo . To enhance the therapeutic efficacy, MSCs are often genetically modified by exogenous genetic transfection based on disease-specific characteristics. ,, To enhance the therapeutic potential of exosomes and improve the prognosis of OA, we used modRNA technology to genetically modify exosomes with Atf5. This study confirmed that Ex modAtf5 released from Gel@Ex modAtf5 were highly effective in preventing OA progression in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, our team documented the benefits of exosomes containing netrin-1 modRNA for the treatment of spinal cord injury. 19 Exosomes derived from cells involve in intercellular material transport and information transmission that exhibit excellent stability, biocompatibility, permeability, and low immunogenicity. 20 Genetically engineered cells can endow exosomes with novel functionalities by delivering bioactive substances, thereby enabling their use as targeted drug delivery vehicles for small molecules, nucleic acids, or drugs to specific cell types or tissues.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions impose an important financial burden on the affected individuals, the respective families and society. Excitotoxicity, neuroinflammation, lipid peroxidation, ischemia–reperfusion injury, and free radical production are key pathological processes and microenvironment imbalances following SCI that impede its repair 1,2 . SCI generally results in sensorimotor and autonomic nerve injuries and is still considered an important public health concern globally.…”
Section: Introductionmentioning
confidence: 99%
“…The complex and diverse pathophysiological processes and microenvironmental imbalances following SCI, including excitotoxicity, lipid peroxidation, neuroinflammation, ischemia-reperfusion injury, and the production of free radicals, 1,2 are the important reasons for the difficult repair of SCI. There are still no effective repair options available.…”
Section: Introductionmentioning
confidence: 99%